Assessment of the 2011 Virginia Earthquake Damage and Seismic Fragility Analysis of the Washington Monument. Issue 4 (November 2016) - Shahidi, S. Golnaz; Pakzad, Shamim N.; Ricles, James M.; Martin, James R.
This paper is concerned with prediction of the probability of occurrence associated with various potential states of damage to the Washington Monument during future seismic events. A finite element model (FEM) of the Monument is developed and updated based on the dynamic characteristics of the structure identified through ambient vibration measurements. The calibrated model is used to study the behavior of the Monument during the 2011 Virginia earthquake. The FEM is modified to have nonlinear material properties to investigate the initiation and propagation of cracking, as well as any compressive crushing in the Monument's shaft during a future earthquake. The nonlinear FEM is subjected to two ensembles of site-compatible ground motions representing different seismic hazard levels for the Washington Monument, and the response used to investigate the probability of occurrence of several structural and nonstructural damage states.